MEDICAL TREATMENT V SURGERY: WHERE DOES MEDICAL TREATMENT END AND SURGERY BEGIN IN TERMS OF SECTION 129 OF THE CHILDREN’S ACT? - Carina van der Westhuizen (Obiter, 2018)
It has been firmly established in South African law that informed consent prior to the commencement of any form of medical procedure is required by the patient, or proxy decision maker. This principle has been established in South African law by two cases, namely Stoffberg v Elliott (1923 CPD 148) and Castell v De Greeff (1994 (4) SA 408 (C)). If the necessary consent is not obtained, the doctor may, among others, incur liability for civil or criminal assault. Initially, consent to the medical treatment of minors was regulated by the Child Care Act (74 of 1983). In terms of section 39(4) of this Act, a minor who reached the age of 18 years was legally competent to consent to an operation while a minor over the age of 14 could independently consent to medical treatment. (This would include a termination of pregnancy, inclusive of an anaesthetic. See Van Oosten “Choice on Termination of Pregnancy Act: Some Comments” 1999 SALJ 67. A termination of pregnancy is performed in terms of the Choice on Termination of Pregnancy Act (92 of 1996) and not the Children’s Act (38 of 2005), therefore it will not be discussed in this note). Van Oosten also notes that neither the terms “medical treatment” nor “operation” are defined in the Child Care Act. The Child Care Act prescribed a cumbersome procedure that had to be followed if the parent or guardian of a child needed to consent to an operation or medical treatment and the responsible person could not be found, could not consent by reason of mental incapacity, refused to consent or was deceased. In such cases the medical practitioner had to report the matter to the Minister of Social Development who could then give proxy consent (s 39(1) of the Child Care Act). In the case of an emergency when an operation or treatment was necessary to save the life of a minor or prevent serious physical injury and a competent person could not be found to consent, the superintendent of the hospital could consent to the necessary procedure (s 39(2) of the Child Care Act). Concerns were raised that the process was cumbersome, led to delays and was therefore not in the interest of minors who need immediate access to medical treatment. As will be pointed out below, the terms “medical treatment” or “surgery” have also not been defined in the Children’s Act. This note therefore seeks to find a workable solution to address the issue of where medical treatment ends and surgery begins as this has an effect on the consent requirements for these procedures. Finally, recommendations will be made based on the research. To put it in context, the consent requirement in the Children’s Act will be discussed, followed by definitions of medical treatment and surgery as well as the way in which other jurisdictions treated the issue of medical treatment and surgery.